Eco-Innovation and Responsibility: The Paris Olympics 2024 and its Impact on City Urbanism - Šmiralová Monika (E3S Web of Conferences)
Paris, host of the 2024 Olympic Games, aims to increase environmental responsibility alongside the integration of sport into urban life. This article analyses the Paris Olympics as a platform for ecoinnovation and reducing the ecological footprint. The construction and renovation is carried out with regard to bioclimatic design principles, the construction of green transport, the use of geothermal energy, measures for the protection and enhancement of the city’s ecosystem etc. This paper will analyse the climate change measures in the metropolis of Paris, which are reinforced by the organisation of the 2024 Summer Olympic Games. At the same time, the findings will be compared with current climate change measures in Slovakia, in particular in the Slovak capital Bratislava.